Enhancing Thermal Performance of a Parabolic Trough Collector with Inserting Longitudinal Fins in the Down Half of the Receiver Tube - LAARABA Adel (My University, 2020)
Heat transfer in a finned absorber of a parabolic trough collector is studied numerically; the main objective of this work is to study the effect of attached fins on the enhancement of the thermal performance of a parabolic trough collector. The values of the fins length are varied from 0 to 20 mm, and their thickness is varied from 0 to 8mm and the number of fins is 5. The parameters us ed in the current study are : the thermal and dynamic field, friction coefficient, Nusselt number , the thermal efficiency and thermal enhancement index .The obtained results indicate that the inclusion of fins to the lower half of the absorber enhance heat t r ansfer in the absorber, the increase of the fins length increase the friction factor , Nusselt number and thermal efficiency, also the increase of fins thickness increase the previous parameters , beyond the value 6 mm of thickness its effect remains the s ame, but thickness is less effective than length. The values 15 mm of length and 6 mm of thickness are selected as optimum values. Finally the inclusion of the fins enhances the thermal performance of t he parabolic collector by 8.45
Intervention
Keywords: solar energy; Nusselt number; thermal efficiency; parabolic trough collector; forced convection.